Evaluasi Sistem Penyaliran Tambang di Pit Yarder Tambang Batubara PT. Kalimantan Prima Persada Jobsite BDMA Kecamatan Malinau Selatan Kabupaten Malinau Provinsi Kalimantan Utara - El Harisaf Taufik; Tamrin Kasim (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. The water that goes to the location of the mining is largely derived from rainwater, which, at the time a high rainfall season cause the puddle on the mining front. Besides that the plan of the progress of the mine will cause in shifting mining front closer to the direction of sump. Because of that would require the re-planning for mine sump dimensions to keep mining activity running optimally. Beside that also required the calculation of pump, pipes, open channel dimension that is able to flow water to the KPL and KPL dimension itself. The rainfall plan processed using Gumbell Method. While the determination of the intensity of the rain with Monnonobe method that will be used to obtain discharge water runoff. So that it can be specified sump dimensions pump needs, open channels dimensions and KPL dimension. Catchment area in Yarder pit PT. Kalimantan Prima Persada Jobsite BDMA, as large as 65,57 hectares. Maximum capacity sump to collect water runoff and groundwater amounted to 116.254,23 m3. Pumping systems were performed using HDPE pipes and pumps used is a centrifugal pump Multiflow MF-420 EXHV, which has a maximum head 220 meter and pump discharge to a maximum of 430 liters / sec as a single unit. Results of pumping flowed into an open channel for later deposited on the mud settling ponds (KPL) with a maximum volume of 10.784 m3.Keywords: Sump, Pump, Open Channel, KPL, Catchment Area